ALTERNATIVE HYPOTHESIS TESTS FOR THE COVARIANCE MATRIX BASED ON EIGENVALUES AND MULTIVARIATE NORMALITY - Mingoti, Sueli Aparecida; Pinto, Letícia Pereira (Brazilian Journal of Operations & Production Management, 2013)